Employee Pay and Benefit Preferences - Jain, Harish; Janzen, Edward (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
Despite a continuing growth of fringe benefits as a proportion of the total wage bill, few employees have any definite knowledge of what fringes employees really prefer. This article reports the results of a study which attempted to measure employees preferences for alternative forms of compensation in six organizations located in Ontario, Canada.